2018
DOI: 10.1186/s12974-018-1113-9
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic impacts of stress priming of the neuroinflammatory response to sarin surrogate in mice: a model of Gulf War illness

Abstract: BackgroundGulf War illness (GWI) is an archetypal, medically unexplained, chronic condition characterised by persistent sickness behaviour and neuroimmune and neuroinflammatory components. An estimated 25–32% of the over 900,000 veterans of the 1991 Gulf War fulfil the requirements of a GWI diagnosis. It has been hypothesised that the high physical and psychological stress of combat may have increased vulnerability to irreversible acetylcholinesterase (AChE) inhibitors leading to a priming of the neuroimmune s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 100 publications
(116 reference statements)
6
32
0
Order By: Relevance
“…The results of the quantitative histological analysis of oligodendroglia in the PFC of the GWI rat model is consistent with RNA‐seq data in mice showing that combined Cort and DFP treatment decreases the fraction of mRNA transcripts associated with mature oligodendrocytes in the PFC (Ashbrook et al, ), but our results are not consistent with this gene profiling study in other respects. Cort treatment alone did not alter the number of mature oligodendrocytes in the PFC, but mRNA transcripts associated with oligodendrocytes are reportedly reduced in this condition (Ashbrook et al, ). Also, the frequency of mature oligodendrocytes in the PFC decreased in response to DFP treatment, but mRNA transcripts associated with mature oligodendrocytes remained unchanged under this condition (Ashbrook et al, ).…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The results of the quantitative histological analysis of oligodendroglia in the PFC of the GWI rat model is consistent with RNA‐seq data in mice showing that combined Cort and DFP treatment decreases the fraction of mRNA transcripts associated with mature oligodendrocytes in the PFC (Ashbrook et al, ), but our results are not consistent with this gene profiling study in other respects. Cort treatment alone did not alter the number of mature oligodendrocytes in the PFC, but mRNA transcripts associated with oligodendrocytes are reportedly reduced in this condition (Ashbrook et al, ). Also, the frequency of mature oligodendrocytes in the PFC decreased in response to DFP treatment, but mRNA transcripts associated with mature oligodendrocytes remained unchanged under this condition (Ashbrook et al, ).…”
Section: Discussionsupporting
confidence: 67%
“…The results of the quantitative histological analysis of oligodendroglia in the PFC of the GWI rat model is consistent with RNA-seq data in mice showing that combined Cort and DFP treatment decreases the fraction of mRNA transcripts associated with mature oligodendrocytes in the PFC (Ashbrook et al, 2018), but our results are not consistent with this gene profiling study in other respects.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Indeed, Trevedi and colleagues [17] showed DNA methylation changes in monocytes from GWI affected veterans in genes related to immune function, thus supporting the hypothesis of neuroimmune sequelae of GWI. In mice, Ashbrook et al [18] showed genome-wide histone modification and DNA methylation in the frontal cortex. Many of the genes so modified are related to myelin production in oligodendrocytes and thus may be related to the observation of reduced white matter in frontal cortex of GWI veterans.…”
Section: Discussionmentioning
confidence: 99%